The impact of anorectal biofeedback therapy on the quality of life of patients with dyssynergic defecation - Şahin, Memduh; Doğan, İbrahim; Cengiz, Mustafa; Ünal, Selahattin (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Dyssynergic defecation is a common health problem affecting the quality of life of patients adversely. We aimed to evaluate the impact of biofeedback therapy on the quality of life of constipated patients due to dyssynergic defecation. Materials and Methods: Constipated patients due to dyssynergic defecation were enrolled to the study. Patients having secondary causes of constipation and who didn’t fulfill the eligible criteria were excluded. All the patients underwent three to ten sessions each of which was thirty minutes biofeedback therapy under the supervision of a trained nurse. After one month the patients were assessed for the control. The impact of biofeedback therapy on the quality of life of patients having dyssynergic defecation was assessed using the validated Medical Outcomes Study Short Form-36 (SF-36) questionnaire before and one month after therapy. Results: Thirty-two patients (20 female 62.5%, 12 male 37.5% and mean age 48 (18-72) underwent three to ten sessions biofeedback therapy. Post-therapy improvements of subscores of SF-36 consists of eight domains were all statistically significant when we compared with the pre-therapy values. Conclusion: This study showed not only the effectiveness of biofeedback as a therapy modality for constipation but also its impact on the improvement of QOL of constipated patients due to dyssynergic defecation. Patients with chronic constipation not improved by dietary fiber and laxatives should be referred to specialized centers that have facilities for further anorectal physiological assessments.